Positron Annihilation Spectroscopy Study on Annealing Effect of CuO Nanoparticles - Jianjian Shi; Jiaheng Wang; Wei Yang; Zhejie Zhu; Yichu Wu (Materials Research, 2016)
The microstructure and defects of CuO nanoparticles under isochronal annealing were investigated by positron annihilation spectroscopy (PAS), X-ray diffraction (XRD) and scanning electron microscope (SEM). XRD and SEM results indicated that the average grain sizes of CuO nanoparticles grew slowly below 800 °C, and then increased rapidly with the annealing temperature from 800 to 1000 °C. Positron lifetime analysis exhibited that positrons were mainly annihilated in mono-vacancies (VCu , VO) and vacancy clusters when annealing from 200 to 800 °C. Furthermore,W-S plot of Doppler broadening spectra at different annealing temperatures found that the (W,S) points distributed on two different defect species, which suggested that V Cu − − V O + complexes were produced when the grains grew to bigger size after annealing above 800 °C, and positrons might annihilate at these complexes.